ESTIMATION OF SHEAR WAVE VELOCITY (VS) USING EARTHQUAKE HORIZONTAL TO VERTICAL SPECTRAL RATIO (EHVSR) METHOD AND AFTERSHOCK DATA FOR CIANJUR 2022 - Daiva Pangestu, Fernanda
On November 21, 2022, a 5.6 magnitude earthquake struck Cianjur, West Java, Indonesia, resulting in numerous fatalities and damage to infrastructure. The earthquake occurred at a depth of approximately 10 km due to indications of conjugate faults in the area. The research aims to characterize the subsurface structure of the Cianjur area using the Earthquake Horizontal to Vertical Spectral Ratio (EHVSR) method. We analyzed aftershock recordings from 19 measuring stations and obtained EHVSR curves from the noise, S-wave, and coda-wave recording sections. When comparing these sections, the S wave section shows a lower dominant frequency and higher amplitude, indicating the presence of a thicker soft soil layer in the region. However, the shape of the coda wave part's curve is similar to that of the noise part. This similarity shows that the waves similarly move in the medium and resonate at almost the same frequency or geological structure. Information on each measurement station's EHVSR curve of the S wave part is carried out. The EHVSR curve is converted to provide a shear wave velocity profile (VS). Based on the EHVSR curve inversion results, Cianjur has a fairly thick structure of hard soil and soft rock, but there is a thin layer of soft soil at several points. At depths of 30 m and 100 m, the material is still quite varied, with indications of less compacted layers, while at a depth of 500 m, the material becomes more uniform and compacted. At a depth of 1000 m, an increase in VS indicates the presence of a denser and harder layer, possibly bedrock. Based on classification, the research area has medium to hard soil